Pengaruh Ekstrak Daun Salam (Syzygium polyanthum Wight) Terhadap Waktu Kematian Ascaris suum,Goeze In Vitro - Gagat Ragil Andaru P; Bambang Sukilarso Sakiman; Sri Haryati (Nexus Biomedika, 2013)
Background: Syzygium polyanthum Wight leaves contain tannin that has been known to have anthelmintic effect. This study aimed to determine the effect of Syzygium polyanthum Wight leaves extract toward death time of Ascaris suum, Goeze In Vitro Methods: The study was a laboratory experimental research using the post-test only controlled group design. Subjects were adult Ascaris suum, Goeze. The sampling technique used was purposive sampling. Subjects were divided into 7 groups, each group consisted of 4 worms, replication was performed 4 times. Saline solution was used in negative control group, pirantel pamoate 5 mg/ml was used in positive control group, while the treatment group used Syzygium polyanthum Wight leaves extract concentration of 70%, 75%, 80%, 85%, and 90%. Worms were immersed in 25 mL of the test solution and incubated at 37C. Observations were done every 1 hour and the number of dead worms was counted. Data were analyzed with regression linier and probit analysis. Results: Observations of total deaths mean time Ascaris suum, Goeze sp on negative control was for 96 hours, on the positive control was for 2 hours 30 minutes, and on the concentration of 70%, 75%, 80%, 85%, and 90% of Syzygium polyanthum Wight leaves extract, each was for 10 hours 15 minutes, 8 hours, 6 hours, 4 hours 45 minutes and 3 hours, consecutively. Linear regression test results showed that the variation of the concentration affected long worm death. Probit analysis results showed that LC50 and LT50 of Syzygium polyanthum Wight leaves extract, each was 76.228% and 3 hours 36 minutes. Conclusions:Based on this study, it could be concluded that of Syzygium polyanthum Wight leaves extract affected mortality of Ascaris suum, Goeze sp in vitro. The increasing of extract concentration was inversely proportional with the death time of worms Keywords: Syzygium polyanthum Wight leaves extract, Ascaris suum,Goeze.